Superhydrophobic electrospun nanofiber membrane coated by carbon nanotubes network for membrane distillation - Yan, Kang-Kang; Jiao, Lei; Lin, Saisai; Ji, Xiaosheng; Lu, Yin; Zhang, Lin (Desalination, 2018)
Electrospun nanofiber membranes (ENMs) have received increasing attentions in membrane distillation (MD) process due to their high porosity and interconnected open pores. However, the hydrophobicity of conventional ENMs depends on the used polymers, and the fabricated ENMs are still wetted during long-term operation. In this article, we present a facile surface coating technique for the fabrication of superhydrophobic ENMs through a spraying method. In this method, the low content of CNTs dispersion with a proper solvent plays an important role to prevent the agglomeration of CNTs. The scanning electron microscopy images showed that the carbon nanotubes (CNTs) were interlaced on polyvinylidene fluoride (PVDF) ENMs and formed a thin network layer. In order to have good bonding force with CNTs, the sprayed ENM was heat-pressed slightly below the PVDF melting point. Because of high hydrophobicity and low surface energy of CNTs, the fabricated membranes exhibited superhydrophobic property. The 20 g/m2 CNTs coated membrane exhibited highest water flux (28.4 kg/m2 h) with steady vacuum membrane distillation (VMD) performance >26 h. The morphology of CNTs coated membranes had no significant change after VMD test. The present study suggests that the CNTs network coated ENMs provide high potential applications towards VMD desalination. [Display omitted] •A simple spraying method to fabricate superhydrophobic electrospun nanofiber membranes is developed.•Low content of CNTs dispersion with a proper solvent is the key factor to prevent agglomerating.•Superhydrophobic CNTs network coated membranes exhibited high anti-wetting performance in VMD.